Proper Hand Washing for Elders - Amy Simonne (EDIS)
Hand washing is an important way to reduce the spread of infectious diseases. Germs from human and animal sources can be transmitted to hands, which can transmit the germs to other people, foods, and anything else that the hands touch. Proper hand washing can reduce the numbers of harmful microorganisms on our hands and reduce the risk of some diseases. This document is FCS 8785-Eng, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date November 2005.